Soil carbon stocks and stability across an altitudinal gradient in southern Peru - Segnini, A.; Posadas, A.; Quiróz, R.; Milori, D.M.B.P.; Vaz Patto, Maria C; Martin Neto, L. (Soil and Water Conservation Society, 2011)
Carbon accumulation and sequestration in Andean soils are scarcely documented. Carbon contents, carbon stocks, and stability were determined in five Peruvian agroecologies, along a 1,000 km (621 mi) transect covering the arid Pacific coast, the Andean high plateau, and the tropical highland rainforest in the eastern flank of the Andes. It was hypothesized that the carbon stocks and stability varied with land use and altitudinal gradient. Results showed that the soils in the tropical highland rainforest site presented the higher (p > 0.05) carbon contents (134 g kg−1 [13.4%]). Coffee plantations in the tropical highland rainforest and alfalfa under irrigation in the dry valleys presented larger (p > 0.05) carbon stocks (83 Mg ha−1 [37 tn ac−1]) than primary rainforests. The dry lowlands showed the lowest carbon contents (51 g kg−1 [5.1%]) and carbon stocks (40 Mg ha−1 [18 tn ac−1]). Soil organic carbon increased with elevation in the arid environments. In the high plateau potato systems, low carbon contents (68 g kg−1 [6.8%]) and carbon stocks (47 Mg ha−1 [21 tn ac−1]) were found. The soils in both the tropical highland rainforest and the dry valleys presented lower humification index, when compared to other agroecologies. Humification increased with soil depth due to the presence of recalcitrant carbon, while at the surface the presence of labile carbon dominates as a result of a constant input of plant residues. Results suggest that diversified production systems with crops and livestock are more stable for carbon stocks, which might be essential to help farmers adapting to the effects of climate change. Therefore, viable land uses, from the carbon economy perspective, must be promoted to support sustainable agricultural practices for most important ecological conditions.